ANALISIS TEKSTUAL BRAND TELUK LOVE MENJADI DESTINASI WISATA POPULER DI KABUPATEN JEMBER - Ari Susanti (MEDIAKOM : Jurnal Ilmu Komunikasi, 2018)
Love Bay, which is located in Payangan Hamlet, Sumberrejo Village, Ambulu District, Jember Regency, is one of the most popular tourist destinations today. The word "Love" is taken from English which means love. The bay shape which resembles a heart is the first thing why the name of “Love Bay” is given to. Why is the Love Bay Brand chosen, among many words like Teluk Cinta, Teluk Hati, Teluk Asmara and others? Therefore, the researcher is interested in analyzing the Brand of Love Bay. This research entitled Textual Analysis of the Brand of Love Bay Becomes a Popular Tourist Destination in Jember Regency was studied using a qualitative descriptive approach using textual analysis techniques. The results of this study are the word "love" in Love Bay has a higher prestige value because it is considered slang and contemporary. From the business perspective, the word "love" is easier to remember as a product brand, it also has a higher selling value because it is very familiar to the public, especially young the juvenile. In addition, the society's perceptions of the word "love" vary in giving rise for the high curiosity and the major attraction for tourists on visiting Love Bay. The role of social media has become one of the factors of success in branding Love Bay as the popular tourist destination in Jember Regency. Keywords: Textual analysis, brand, a tourist destination